Harnessing Waste Heat from Indoor lamps for Sustainable Thermocatalytic Mineralization of Acetaldehyde using Platinized TiO2. (December 2022) - Lee, Minhyung; Yim, Heewon; Kim, Bupmo; Kim, Suho; Choi, Wonyong; Kim, Wooyul; Kim, Hyoung-il
Abstract: This study demonstrates the first reported thermocatalytic oxidation of an indoor volatile organic compound (VOC), acetaldehyde, by harnessing the waste-heat energy from indoor light sources (e.g., halogen lamps) without additional energy inputs. With an optimal Pt–TiO2 catalyst, the designed catalyst-coated lampshade was successfully activated under waste-heat energy (∼120 °C) and achieved the complete mineralization of CH3 CHO into CO2 ( k  = 0.02 min −1 ). The catalytic activity of Pt–TiO2 was extremely dependent on its preparation method which greatly influenced the characteristics (e.g., oxidation state and size) of Pt. The thermocatalytic oxidation mechanism of CH3 CHO over Pt–TiO2 was investigated, which revealed that O2 and H2 O sources play vital roles. Although Pt is an expensive noble metal, the thermocatalytic process on the Pt–TiO2 -coated lampshade without additional energy, along with its outstanding activity, can offset the high material cost. The proposed strategy offers a sustainable and feasible method for the degradation of indoor VOCs. Graphical abstract: Lee et al., "Harnessing Waste Heat from Indoor lamps for Sustainable Thermocatalytic mineralization of Acetaldehyde using Platinized TiO2 ". Image 1 Highlights: First reported thermocatalytic acetaldehyde removal by harnessing indoor waste heat. Pt–TiO2 was coated on lampshades to utilize heat energy from indoor light sources. Thermocatalytic activity is greatly influenced by the oxidation state of Pt. Transmission FT-IR revealed roles of O2 and H2 O on thermocatalytic CH3 CHO oxidation.